2019
DOI: 10.24251/hicss.2019.099
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Gamification, Brand Engagement and Brand Equity

Abstract: Many companies are increasingly attempting to build and manage brand communities that increasingly resemble games and game communities and believe that this gamification can increase the engagement and loyalty of consumers to the brand. However, currently, there is a dearth of empirical evidence supporting these expectations in the realm of marketing beyond the pervasive hype around gamification. Therefore, in this study, we investigate the relationship between gamification features, brand engagement and brand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 52 publications
1
27
0
1
Order By: Relevance
“…For example, Yang et al [9] found that perceived usefulness influences intention to engage with the game and the attitude towards the gamified brand, and hence is the strongest predictor to brand attitude. A similar study by Nannan and Hamari [16] was conducted regarding gamification and brand engagement. In another research by Hwang and Choi [15], the authors realized that gamification increases consumer loyalty, which in turn results in increased consumer participation.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…For example, Yang et al [9] found that perceived usefulness influences intention to engage with the game and the attitude towards the gamified brand, and hence is the strongest predictor to brand attitude. A similar study by Nannan and Hamari [16] was conducted regarding gamification and brand engagement. In another research by Hwang and Choi [15], the authors realized that gamification increases consumer loyalty, which in turn results in increased consumer participation.…”
Section: Introductionmentioning
confidence: 94%
“…However, because the majority of e-commerce researches has been done before the emergence of gamification, the impact of the gamification on customer purchase satisfaction has been ignored. In recent researches, the effect of gamification has been seen as a key factor in E-customer loyalty [9]- [16]. For example, Yang et al [9] found that perceived usefulness influences intention to engage with the game and the attitude towards the gamified brand, and hence is the strongest predictor to brand attitude.…”
Section: Introductionmentioning
confidence: 99%
“…In the gamified mHealth domain, challenges help users satisfy their intrinsic need for competence after completing a demanding task. The limited literature suggests that challenges positively relate to intrinsic need satisfaction in a gamified system [ 62 ]. Moreover, challenges have been shown to assist users in reaching their fitness goals in mHealth [ 63 ].…”
Section: Research Model and Hypotheses Developmentmentioning
confidence: 99%
“…Previous studies recommended that customers have a higher level of enjoyment while collecting points and badges (Codish and Ravid, 2017 ). By achieving a specific assignment, consumers collects points, gets identification updates, and encounters a sensation of euphoria, fun, and enjoyment (Denny, 2013 ; Xi and Hamari, 2019 ). As indicated by Lazzaro ( 2009 ), there are four kinds of entertainment: easy fun, based on curiosity; serious fun, based on the excitement of obtaining valuable objects; people fun, based on social connections; and hard fun, based on challenges that require strategy and skill.…”
Section: Research Model and Hypothesis Developmentmentioning
confidence: 99%